2020
DOI: 10.1111/jch.14059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlates of ambulatory blood pressure phenotypes in a Saudi hypertensive population

Abstract: International Guidelines recommend ambulatory blood pressure monitoring (ABPM) for the management of hypertension. ABPM phenotypes predict outcomes independent of office blood pressure (BP). The authors explored the prevalence and clinical correlates of ABPM phenotypes and relationship with office BP in Saudi patients (n = 428, mean age 53.5 ± 14.6, 55% male) referred to a Specialist Hypertension clinic in Riyadh, Saudi Arabia. ABPM phenotypes included sustained normotension (27%), masked hypertension, MHT(32%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“… 6 In 428 Saudi patients who were referred to a hypertension clinic, INH was observed in 21%, and was more prevalent in masked hypertension versus sustained hypertension (70% vs 30%, P < .001) and in untreated versus treated patients (29% vs 18.7%, P < .05). 5 In a recent report from a Korean general population including 823 participants, INH was observed in 22.8% of patients, among whom 92.6% had normal office BP. 3 Compared to normotensive participants, the INH patients had an older age, greater body mass index, and higher levels of serum cholesterol and plasma glucose, and serum creatinine.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 6 In 428 Saudi patients who were referred to a hypertension clinic, INH was observed in 21%, and was more prevalent in masked hypertension versus sustained hypertension (70% vs 30%, P < .001) and in untreated versus treated patients (29% vs 18.7%, P < .05). 5 In a recent report from a Korean general population including 823 participants, INH was observed in 22.8% of patients, among whom 92.6% had normal office BP. 3 Compared to normotensive participants, the INH patients had an older age, greater body mass index, and higher levels of serum cholesterol and plasma glucose, and serum creatinine.…”
Section: Discussionmentioning
confidence: 95%
“…Patients with INH had a significantly higher neck circumference than normotensive persons 6 . In 428 Saudi patients who were referred to a hypertension clinic, INH was observed in 21%, and was more prevalent in masked hypertension versus sustained hypertension (70% vs 30%, P < .001) and in untreated versus treated patients (29% vs 18.7%, P < .05) 5 . In a recent report from a Korean general population including 823 participants, INH was observed in 22.8% of patients, among whom 92.6% had normal office BP 3 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies on ABPM have mainly focused on outpatients or inpatients ( 16 18 ), and the number of studies on the population receiving primary health care is very limited. ABPM is not routinely used in primary health care due to its high cost and limited resources ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have found that the incidence of masked hypertension, morning hypertension and nocturnal hypertension in Asian countries is higher than that in Western countries ( 7 9 ). However, the use of ABPM in Asian countries, including China, is very limited, especially in primary health care ( 10 ). The purpose of this study was to compare OBP with ABPM in high hypertension-risk Asian individuals in primary care.…”
Section: Introductionmentioning
confidence: 99%